Tren Penelitian Komunikasi Islam di Indonesia: Analisis Bibliometrik Berbasis Data Scopus - Muhammad Choirin; Hadiyan; Tajudin; Maulan, Rikza; Kurniawan; Idris, Indriyani (Jurnal Komunikasi Islam, 2024)
This study explores the evolution of Islamic communication studies in Indonesia as documented in prestigious Scopus-indexed journals from 2016 to 2024. This research employs a bibliometric approach and focuses on keyword analysis from eight selected journals to identify trends, publication patterns, author and institutional contributions, and the dominant themes within Islamic communication research in Indonesia. Data analysis includes the number of publications, citation counts, and collaboration networks among researchers. The findings reveal that while still limited, publications in the field of Islamic communication have grown over the past nine years, with key themes such as marketing, literacy, business, tourism, banking, and finance emerging as dominant focus areas. Additionally, the study highlights an increasing trend in author collaboration, at the national and international levels. These insights offer a comprehensive overview of the developmental trajectory of Islamic communication research in Indonesia, providing valuable guidance for future research and fostering further collaboration and innovation among scholars in this field.